Bahasa Pijin Mahasiswa Thailand di Kota Tangerang Provinsi Banten - Ira Anisa Purawinangun; Irpa Anggriani Wiharja (LP4MK STKIP PGRI Lubuklinggau, 2019)
The aim of this research was to describe the pidgin language of Thailand students who lived in Tanggerang. The data in this research was the forming of new language from some others languages or it is called as pidgin. This research had two types of data; primary and secondary data. Primary data was the result of interview. While, secondary data was all references that relevance to the research. Due to the research problem, the qualitative descriptive research design was used. There were some techniques used to collect the data such as observation, interview, and documentation. In this research, the content analysis data analysis method was also used. So, based on the analysis of data, the result of the research was pidgin as the simplify of language form. For example, morpholgy form, syntax, tolerance of phonology variance, reduction of some function, and absorption of language from other languages.